Ownership Of The Right To An Apartment Unit By A Foreign Citizen After The Enactment Of The Job Creation Law - Ilham Nugroho; Imam Koeswahyono; Hanif Nur Widhiyanti (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The Law No.11 of 2020 On Job Creation is a new law that aims to facilitate investment initiated by the government of President joko widodo, in the regulation has expanded the rights to apartment units by foreign citizens. In this context, the issuance of these regulations is important to ensure legal certainty, justice and expediency. This article explores the expansion of property rights to the unit flats associated with the principle of nationality in Law No. 5 of 1960 on agrarian principles. In the expansion of property rights to units of flats by foreign nationals in the job creation law should not ignore what is the purpose of the construction of flats in Indonesia.